Supporting new strategic models of science-industry R&D collaboration: A review of global experiences - Henning Kroll (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2016)
In recent years, an increasing political interest has developed in long-term strategic partnerships for science-industry collaboration in pre-competitive research and devel-opment, driven by a perception of a distinct "blind spot" in many innovation systems. In different contexts, such initiatives have been politically supported based on different factual opportunities and according to the options available in specific political frame-works. Nonetheless, the lessons to be learned from them are not by definition idiosyn-cratic. Against this background, this paper synthesises experiences from different countries and derives generalisable conclusion with regard to the both the nature of the phenomenon and opportunities for future policy actions to promote its development. In short, it finds that viable initiatives tend to be stakeholder driven and policy pro-grammes have to reflect this in selecting competitively, raise clear expectations and endow individual initiatives with strategic capacity.
urn:nbn:de:0011-n-3796784
Keywords: 330